Prospective elementary teachers’ informal mathematical proof using GeoGebra: The case of 3D shapes - Putra, Zetra Hainul; Afrillia, Yesi Martha; Dahnilsyah; Tjoe, Hartono (Universitas Sriwijaya in collaboration with Indonesian Mathematical Society (IndoMS), 2023)
Mathematical proofs play a paramount role in developing 21st-century skills, and the use of technology in mathematics learning has widely paved the way in the instruction of mathematical proofs. In mathematics education, GeoGebra has a significant role as a dynamic mathematics software in supporting students' learning process. This study aims to use GeoGebra in supporting prospective elementary teachers' mathematical proofs of the volume of 3-D shapes. This research used a case study method with 23 first-year prospective elementary teachers as participants from a public university in Riau, Indonesia. The data were gathered by means of students' work recordings in the GeoGebra classroom and video recordings from their interactions in the course of small group and classroom discussions. The videos were transcribed using verbatim, and then the mathematical proofs were analyzed using praxeological analysis. The findings show that prospective elementary teachers still had challenges to connect the construction of the volume of 3-D shapes using GeoGebra to its informal mathematical proofs. However, GeoGebra provides an opportunity to learn informal mathematical proofs for prospective elementary teachers.